An Index to Qualitative Screening of Phytochemicals in Homoeopathic Remedies (Homoeopathy for All, 2025)
In the realm of homeopathic pre scribing, efficacy is intricately tied to the purity and quality of both raw materials and the final remedies. A deviation from standards can signifi cantly impact therapeutic outcomes. Drug standardization, a cornerstone of homeopathy, involves a compre hensive evaluation encompassing pharmacognostical, physico-chem ical, and pharmacological param eters. This theoretical descriptive article delves into the intricacies of tests for qualitative and quantitative analysis in homeopathic drug stan dardization. By providing a theoreti cal framework, this article aims to deepen understanding of the phyto chemical screening tests utilized in drug standardization.
Keywords: Phytochemical screening; Homoeopathy, Homoeopathic drugs; Standardisation; Qualitative analysis